A bibliometric analysis and visualization of non-suicidal self-injury in adolescents - Luo, Jingtong; Yang, Xueru; Li, Hongli; Fan, Lin; Chen, Xuehe; Li, Jiayi; Song, Tianming (Frontiers in Psychiatry, 2024)
Background: Non-suicidal self-injury(NSSI)is a widespread occurrence among adolescents, and this behavior can bring serious consequences. In recent years, the prevalence of NSSI continues to rise, which has attracted the attention of many researchers. But currently there is no research exploring the overall research distribution of NSSI in adolescents through quantitative analysis. Therefore, it is necessary to understand the status of development and main research hotspots of NSSI in adolescents via bibliometric analysis. Methods: We searched the relevant studies from the Web of Science Core Collection(WoSCC) from January 1, 2014 to December 31, 2023. Using CiteSpace and VOSviewer visual analysis tools, we analyzed studies from the perspectives of country, region, institution, journal, author, and keywords. Result: A total of 2177 studies related to NSSI in adolescents were included. USA and Harvard University were the leading country and institution in this research field. Penelope Hasking was the most prolific author. Frontiers in Psychiatry and the Journal of Affective Disorders were the most productive journals. The most high-frequency keywords were 'depression', 'mental health', 'emotion regulation' and 'borderline personality disorder'. 'mindfully', 'intervention', 'selfcompassion' and 'ecological momentary assessment' were the emerging keywords. Conclusions: Exploring the relevant factors and mechanisms of comorbidities, identifying etiology and risk/protective factors, and finding the impact of NSSI on adolescents are the hot topics. Moreover, intervention measures and interdisciplinary collaborative research for NSSI in adolescents will emerge as frontiers in the future.